A Novel Large Animal Model of Acute Respiratory Distress Syndrome Induced by Mitochondrial Products. Issue 6 (December 2017) - Sanchez, Pablo G.; Pasrija, Chetan; Mulligan, Matthew J.; Wadhwa, Mandheer; Pratt, Diana L.; Li, Tieluo; Gammie, James S.; Kon, Zachary N.; Pham, Si M.; Griffith, Bartley P.
Abstract : Objective: We aimed to create a reproducible lung injury model utilizing injection of mitochondrial damage-associated molecular products. Our goal was to characterize the pathophysiologic response to damage-associated molecular pattern mediated organ injury. Summary Background Data: There remain significant gaps in our understanding of acute respiratory distress syndrome, in part due to the lack of clinically applicable animal models of this disease. Animal models of noninfectious, tissue damage-induced lung injury are needed to understand the signals and responses associated with this injury. Methods: Ten pigs (35–45 kg) received an intravenous dose of disrupted mitochondrial products and were followed for 6 hours under general anesthesia. These animals were compared to a control group (n = 5) and a model of lung injury induced by bacterial products (lipopolysaccharide n = 5). Results: Heart rate and temperature were significantly elevated in the mitochondrial product (204 ± 12 and 41 ± 1) and lipopolysaccharide groups (178 ± 18 and 42 ± 0.5) compared with controls (100 ± 13 and 38 ± 0.5) ( P <0.05). Lung oxygenation (PaO2 /FiO2 ) was significantly lower 6 hours after injection in the mitochondrial products and lipopolysaccharide groups compared with controls (170 ± 39, 196 ± 27, and 564 ± 75 mm Hg respectively, P = 0.001). Lung injury scoring of histological sections was significantly worse in mitochondrial and lipopolysaccharide groups compared with controls (mitochondrial-64 ± 6, lipopolysaccharide-54 ± 8, control-14 ± 1.5, P = 0.002). Conclusions: Our data demonstrated that the presence of mitochondrial products in the circulation leads to systemic inflammatory response and lung injury. In its acute phase lung injury induced by tissue or bacterial products is clinically indistinguishable. Abstract : Supplemental Digital Content is available in the text